Human Rights in Hong Kong - Cooke, Robin (Victoria University of Wellington Law Review, 1999)
In this address to the UNDR commemorative seminar in April 1998 Lord Cooke speaks of human rights, his current judicial roles and the prospects for a common law of the world. Lord Cooke discusses the importance of human rights law in both substance and implementation. The author reports on the process of implementing constitutional law and human rights in New Zealand, Samoa, the Republic of Fiji, the United Kingdom, and Hong Kong.